Clinical Profile of Patients with Pleural Effusion Admitted to Bharatpur Hospital - Agrahari, Mahendra; Sapkota, Kalyan; Singh, Ranjita; Dahal, Prajawal; Shrestha, Joon Kumar (Journal of National Heart and Lung Society Nepal, 2023)
ABSTRACT Background: Pleural effusion occurs when there is disequilibrium between the quantity of fluid entering and leaving the pleural space. The objective of the study was to investigate the association between pleural effusion and underlying medical conditions as heart failure, pneumonia, malignancies of clinical presentations and laboratory findings of all those patients admitted to Bharatpur Hospital during the period of last 1year. Methods: Retrospective data from September 2022 to September 2023 from all the cases diagnosed with pleural effusion will be taken. Altogether 120 cases diagnosed with pleural effusion studied. The collected data was re-checked, reviewed, organized, entered and analyzed in statistical package for social sciences (SPSS) version 20.0. Results: From the findings of the study, 56.7% were male and 60.0% were from outside Chitwan District. Among the various causes of pleural effusion the most common cause was tubercular effusion (30.8%) followed by para-pneumonic effusion (19.2%). Tubercular effusion is Shortness of breath was present in 13.5%, cough in 10.8%. Tubercular pleural effusion is common in the age group 41–50 years and Patients with para-pneumonia, is 97 had lymphocyte and 23 had neutrophil. >3 gm/dl was observed in patients with tubercular effusion and Mean value of ADA for tubercular effusion was 45.8 U/L. Conclusions: Our study concluded that shortness of breath, cough, and Pleural fluid analysis is the diagnostic method to distinguish exudative from transudative pleural effusion. Lymphocyte rich exudative effusion occurs in case of Tubercular effusion and neutrophil rich effusion occurs in para-pneumonic effusion. Key words: pleural effusion, exudative, transudative.